Phosphorylation of eukaryotic initiation factor eIFiso4E enhances the binding rates to VPg of turnip mosaic virus. - Mateen A Khan (Public Library of Science (PLoS), 2021)
Binding of phosphorylated eIFiso4E with viral genome-linked protein (VPg) of turnip mosaic virus was examined by stopped-flow, fluorescence, circular dichroism (CD) spectroscopy, and molecular docking analysis. Phosphorylation of eIFiso4E increased (4-fold) the binding rates as compared to unphosphorylated eIFiso4E with VPg. Stopped-flow kinetic studies of phosphorylated eIFiso4E with VPg showed a concentration-independent conformational change. The dissociation rate was about 3-fold slower for eIFiso4E∙VPg complex upon phosphorylation. Phosphorylation enhanced the association rates and lowered the dissociation rates for the eIFiso4E∙VPg binding, with having higher preferential binding to eIFiso4Ep. Binding rates for the interaction of eIFiso4Ep with VPg increased (6-fold) with an increase in temperature, 278 K to 298 K. The activation energies for binding of eIFiso4Ep and eIFiso4E with VPg were 37.2 ± 2.8 and 52.6 ± 3.6 kJ/mol, respectively. Phosphorylation decreased the activation energy for the binding of eIFiso4E to VPg. The reduced energy barrier suggests more stable platform for eIFiso4Ep∙VPg initiation complex formation, which was further supported by molecular docking analysis. Moreover, far-UV CD studies revealed that VPg formed complex with eIFiso4Ep with substantial change in the secondary structure. These results suggested that phosphorylation, not only reduced the energy barrier and dissociation rate but also enhanced binding rate, and an overall conformational change, which provides a more stable platform for efficient viral translation.